Complications and Hardware Failure Following Synthetic Cranioplasty Implants and Free Flap Coverage - Oleck, Nicholas C.; Zhang, Kevin K.; Shammas, Ronnie L.; Nelson, Jonas A.; Allen, Robert J., Jr.; Matros, Evan; Geng, Yisong; Sergesketter, Amanda R.; Naga, Hani I.; Erdmann, Detlev; Phillips, Brett T. (Journal of Reconstructive Microsurgery, 2025)
Composite defects of the scalp and calvarium are complex reconstructive problems. Bony reconstruction is often achieved with synthetic implants, demanding robust soft tissue coverage. In cases where the native scalp has been compromised, free tissue transfer may be indicated. The existing literature on this topic lacks a robust analysis of long-term outcomes and hardware retention rates. The current study is a multi-institutional review of composite calvarial reconstruction with free flap coverage of synthetic cranioplasty implants, focusing specifically on flap selection, long-term outcomes, hardware extrusion, and explantation rates.A retrospective review was conducted at two high-volume institutions for patients who had undergone cranioplasty and free tissue transfer between 2001 and 2022. Patient demographics and comorbidities, reconstructive indications, cranioplasty material, flap type, and complications within a 90-day period were collected. Implant exposure and explantation data were collected through follow-up.A total of 42 patients were identified with an average age of 59 years (SD 14.9). Prior scalp radiation was present in 54.7% of cases. Cranioplasty was most commonly indicated after tumor extirpation (88.0%), with titanium mesh as the most common material utilized (64.3%). The most commonly used free flaps were latissimus (45.2%), anterolateral thigh (ALT) (16.7%), and radial forearm (16.7%). The most common recipient vessels were the superficial temporal (64.2%), facial (21.4%), and superior thyroid (9.5%). Flap compromise requiring return to the operating room occurred in two patients (4.8%) and partial flap loss occurred in three patients (7.14%). Surgical complications occurred in 60% of cases with wound complications (33.3%) and surgical site infection (28.6%) being the most common. Implant extrusion occurred in 31% of cases at an average of 7.9 months (SD 30.1) after definitive reconstruction, and explantation was required in 42.9% of cases at an average of 12.8 months (SD 33.6). The average total length of follow-up was 27.1 months.This multi-institutional analysis found that patients who undergo composite cranial vault reconstruction and free flap coverage experience high rates of surgical complications, and over one-third of these patients experience implant extrusion or explantation. Although no individual patient-related risk factor was independently associated with increased complication rates, our findings suggest that flap composition and timing of reconstruction may influence hardware retention and should be carefully considered during preoperative planning.
Keywords: cranioplasty; scalp reconstruction; free flap scalp reconstruction